Структура земельних угідь в ландшафтно-екологічній організації території Волинської області - Павловська, Тетяна Сергіївна; Pavlovska, Tetyana S. (Таврійський національний університет, 2014)
У статті відображено результати оцінювання структури землекористування Волинської області в розрізі адміністративних районів. Здійснено порівняльний аналіз нинішньої структури земельного фонду і рекомендованих екологічних параметрів збалансованої територіальної організації.In the article the results of evaluation of structure of land-tenure of the Volyn region are represented according to administrative districts. The comparative analysis of present structure of the land fund and recommendable ecological parameters of the balanced territorial organization are carried out. Landscape-ecological priorities of development of territory of the Volyn region were certain for this purpose. The coefficient of ploughed lands, percentage of ploughed lands, level of the agricultural development, correlation of natural and economic lands of administrative districts of the Volyn region are analyzed. On the calculated indexes skeleton maps of their spatial distribution are created. On correlation of natural and economic lands the typology of administrative districts of Volyn is executed. The skeleton map created on the results of the conducted typology gave an opportunity to distinguish three natural areas of groups in administrative districts. The natural area of optimal correlations of natural and economic lands is belonged to the Polesian lowland (Liuboml, Shatsk, Stara Vyzhivka, Ratne, Kovel, Kamin-Kashyrskyi, Lyubeshiv, Manevichi and Kivertsi districts). The natural area with the relatively optimal indexes of this criterion includes the extreme south of the Polesian lowland and partly north of Volyn highland (Volodymyr-Volynskyi, Turyisk, Rozhysche districts). The natural area of unfavorable correlations of the lands is timed to the highlanded forest-steppe part of region (Ivanychi, Lokachi, Horokhiv, Lutsk districts). The basic factors of the existing situation are historical features of settling of territory, differences in the natural conditions and resources of Polesian and forest-steppe parts of the region. For more detailed ecological diagnosis of territory of the Volyn region the evaluation of ecological coefficients of balanced of territorial structure (coefficients of ecological stability, anthropogenic loading, absolute tension, relative tension, to ecological security etc.) is needed. Those points determine the prospects of our further researches.
The structure of the lands in landscape-ecological organization of territory of the Volyn region
Keywords: екологічно сталі ландшафти; коефіцієнт розораності; ландшафтно-екологічна оптимізація території; ландшафтно-екологічні пріоритети розвитку території; лісистість; рівень сільськогосподарської освоєності; розораність сільськогосподарських угідь; структура земельного фонду; ecologically stable landscapes; coefficient of ploughed lands; landscape-ecological optimization of territory; landscape-ecological priorities of development of territory; percentage of forest land; level of the agricultural mastering; percentage of ploughed agricultural lands; structure of the land fund